O desafio de inclusão social do trabalhador em um mercado de trabalho transicional: da flexicurity a um paradigma de Estado Social? - Henrique de Almeida Carvalho (2017)
Is it possible to conceive the development of a Social State by harmonizing the antagonisms inherent in the capital/labour conflict? What is the basis for the idea of equalizing the labour markets by reformatting its flexibility and security dimensions? The emergence of the conceptions of transnational interaction and globalized capitalism triggered an intense process of deconstruction of the (successful) paradigm of welfare states, closely linked to the "malfunctioning" of labour markets. The instability of the traditional protectionist institutions and the failure to ensure equality and social justice resulting from that were the backdrop for the drafting of new proposals for the reformulation of social and employment policies at the heart of the European Union, specially developed from the premises established by theories of transitional labour markets and flexicurity, objects of study of the dissertation. The phenomenon of modelling the solutions presented by the Scandinavian countries to the failure of welfare systems, which, in opposition to the voices announcing the emergence of another veiled manoeuvre of the neoliberal agenda, was launched as a bulwark of the European employment strategy, will be confronted with the dilemma of the segmentation of the labour market in search of new advances for the endeavor of social inclusion in contemporary capitalism.